2012
DOI: 10.1039/c1cp22774b
|View full text |Cite
|
Sign up to set email alerts
|

Non-photochemical laser-induced nucleation of supercooled glacial acetic acid

Abstract: Non-photochemical laser-induced nucleation (NPLIN) of glacial acetic acid (GAA) is demonstrated. The fraction of samples nucleated depends linearly on peak laser power density at low powers (<100 MW cm(-2)) with a threshold of (9.0 ± 4.2) MW cm(-2); at higher laser powers the fraction reaches a plateau of 0.75 ± 0.24 (2σ uncertainties). A simple model based on polarizability of pre-nucleating clusters gives a value of the solid-liquid interfacial tension γ(SL) = 15.5 mJ m(-2). It is hoped that the results will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 33 publications
4
46
0
2
Order By: Relevance
“…These phenomena are often referred to as nonphotochemical laser induced nucleation (NPLIN). 4,5 Our consideration is based on the classical nucleation theory, [6][7][8] according to which, the change in free energy is the sum of the bulk and surface contributions and an electric field dependent term, F E ,…”
mentioning
confidence: 99%
“…These phenomena are often referred to as nonphotochemical laser induced nucleation (NPLIN). 4,5 Our consideration is based on the classical nucleation theory, [6][7][8] according to which, the change in free energy is the sum of the bulk and surface contributions and an electric field dependent term, F E ,…”
mentioning
confidence: 99%
“…In the case of NPLIN using pulsed lasers, the light is delivered to the sample over a very short time (o100 ns). 30,31 Nucleation can be effected with a single laser pulse. 32,33 Typically the beam is not focussed tightly, so as to avoid optical breakdown or photochemical effects.…”
mentioning
confidence: 99%
“…Laser-induced nucleation experiments have a been carried out previously in a variety of metastable (supersaturated) solutions [1][2][3][4][5]17,52 but a mechanistic understanding of the phenomenon has been lacking. We surmised that laser-induced nucleation was caused by optical trapping near a liquid-liquid critical point.…”
Section: Laser-induced Phase Separation (Lips)mentioning
confidence: 99%
“…1 Most excitingly, it was reported that the laser polarisation could be used to control which polymorph would nucleate, promising an unprecedented degree of control. 2,3 Subsequent work showed that laser pulses can induce nucleation of various crystals, [4][5][6][7][8] liquid crystals 9,10 and bubbles. 11 However, these nanosecond-laser nucleation experiments defied all explanation.…”
Section: Introductionmentioning
confidence: 99%